Econometric Estimates of Russia's Turn to the East - A. A. Baykov; V. A. Gnevasheva (Vestnik MGIMO-Universiteta)
The emerging trend in Russia’s foreign policy is its reorientation from active interstate and socio-economic interaction with the states of the "collective West" to the countries that make up the Asian macroregion. The article presents the qualitative and quantitative assessment of the emerging relations between Russia and the countries of the East, namely the ASEAN countries, Northeast Asia and the Indo-Pacific region. Assuming that the prerequisites for the strengthening of such relationships between countries should be reflected in changes in trade relations, increased migration flows, and changes in policy in terms of countries' military spending, the study attempts to evaluate such changes econometrically. We use the method of constructing multiple linear regression, as well as indicators for assessing country-by-country correlation and cluster analysis. The object of the research is the countries of Northeast Asia (China, Japan, Republic of Korea); ASEAN countries (Thailand, Indonesia, Vietnam, Malaysia, Singapore); India; Australia and Oceania. The empirical base of the study is the official statistics of World Bank, SIPRI, FSGS. The findings indicate the emerging conditions for Russia's turn to the East. The analysis reveals a number of stable features indicating the possibility of modeling a reasonable predictive scenario. The proposed estimates can also be used for further study of the directions of interaction between Russia and the East, methodological and empirical clarification of the emerging relationships, determination of significant factors strengthening the noted interactions.